2024
DOI: 10.1128/spectrum.02994-23
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent effect of plant secondary metabolites on bacterial and fungal microbiomes in caterpillar guts

Hana Šigutová,
Petr Pyszko,
Martin Šigut
et al.

Abstract: Plant–herbivore interactions have been modulated by plant secondary metabolites (PSM), which exert a strong pressure on herbivore microbiome. This study examined the effects of different PSM types and concentrations on caterpillar fitness, composition of gut bacterial and fungal assemblages, and microbiome network stability and symbiotic bonds in relation to the caterpillar diet breadth. Polyphagous and monophagous caterpillars sampled from oak were reared on an artificial diet (AD) containing PSM native (tann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 114 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…Studies by other scientists have shown that secondary compounds protect trees against the hazardous effects of herbivorous insects [ 38 , 44 ]. The concentrations of secondary metabolites, such as terpenes and polyphenols, which exert a significant influence on the feeding performance of phytophagous insects [ 45 ], increase following insect damage in woody plants [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by other scientists have shown that secondary compounds protect trees against the hazardous effects of herbivorous insects [ 38 , 44 ]. The concentrations of secondary metabolites, such as terpenes and polyphenols, which exert a significant influence on the feeding performance of phytophagous insects [ 45 ], increase following insect damage in woody plants [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%